2018
DOI: 10.1016/j.jcis.2018.06.056
|View full text |Cite
|
Sign up to set email alerts
|

Novel electrochemical synthesis of copper oxide nanoparticles decorated graphene-β-cyclodextrin composite for trace-level detection of antibiotic drug metronidazole

Abstract: Over the past decades, the synthesis of inorganic and organic nanocomposites has received much attention in the range of fields including electroanalysis of organic chemicals. In this regard, we have prepared copper oxide nanoparticle (CuO NPs) decorated graphene/β-cyclodextrin (GR-β-CD) composites using a simple electrochemical methodology, where the CuO NPs are electrodeposited on GR-β-CD composite modified electrodes. A stable GR-β-CD composite was prepared by sonication of GR in β-CD aqueous solution. As-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Copper, a low-cost transition metal, and its oxides have received signicant attention in the scientic community because of their interesting electronic and surface structures, excellent redox, high catalytic activity, as well as antifungal and antifouling properties. [12][13][14][15] With such unique properties, copper-based NMs have been widely used in sensors, 16 photocatalysis, 17 and antimicrobial applications. 15 Copper nanoparticles (Cu-NPs) were developed in electrochemical sensors to take advantage of their inherent merits, such as conductivity, excellent redox, and cost-effectiveness in comparison with other noble metal NPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Copper, a low-cost transition metal, and its oxides have received signicant attention in the scientic community because of their interesting electronic and surface structures, excellent redox, high catalytic activity, as well as antifungal and antifouling properties. [12][13][14][15] With such unique properties, copper-based NMs have been widely used in sensors, 16 photocatalysis, 17 and antimicrobial applications. 15 Copper nanoparticles (Cu-NPs) were developed in electrochemical sensors to take advantage of their inherent merits, such as conductivity, excellent redox, and cost-effectiveness in comparison with other noble metal NPs.…”
Section: Introductionmentioning
confidence: 99%
“… 16 Cupric oxide nanoparticles (CuO-NPs), as a semiconductor, were used to improve the electrocatalytic activity of graphene-modified electrodes in the electrochemical sensor for the determination of metronidazole. 13 Cuprous oxide nanoparticles (Cu 2 O-NPs), as a typical p-type semiconductor, which integrated with rGO for electrochemical detection of dimetridazole, also showed significant improvement in the electrocatalytic activity towards dimetridazole. 18 The current reviews of NMs-based electrochemical sensors for antibiotics have indicated that hybrid structures, especially the 2D NMs-based hybrid structures, are strong candidates in the development of advanced electrochemical sensors.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, copper oxide nanoparticles doped graphene(GR)-β-CD composites have been reported for the detection of metronidazole as an antibiotic drug (Figure 37). 272 The fabricated electrode displayed a linear electrochemical response between 0.002 and 210.0 µM concentration range and 0.6 nM metronidazole detection limit. The electrochemical results…”
Section: Biosensor Applications Of β-Cyclodextrin-based Nanocompositesmentioning
confidence: 95%
“…The types of nanomaterials adopted for the determination of antibiotics are as follows. Among them, 0D materials include nanoclusters (Zang et al, 2013 ), nanoparticles (Wu et al, 2018 ), and quantum dots (QDs) (Malik et al, 2019 ); the 1D materials include nanowires (Shad et al, 2019 ), nanotubes (Xiao et al, 2007 ), and nanorods (Roushani and Ghanbari, 2018 ); the 2D materials include nanoflakes (Zeng et al, 2018 ) and nanofilms (Velusamy et al, 2018 ).…”
Section: The Role Of Nanomaterials In Antibiotics Detectionmentioning
confidence: 99%